THE ROLE OF GEOGRAPHICAL INDICATIONS ON CITY BRANDING - Elif Pınar Başkaya; Ayça Can Kırgız (Annals of the University of Craiova: Economic Sciences Series, 2020)
In todays globalizing world, competition is not only among products, services or companies, but also between countries and cities. From this point of view, it is important that cities that want to gain advantage against to their competitors, should put forward their own features that play an important role in being a brand and to go to benefit from these features. Geographical indications (GI) are marks indicating the origin of a product that shows a product identified with a locality, area, region or country of origin with a distinctive characteristic feature, reputation or other qualities. As this study investigates the role of food products protected under geographical indications on city branding. The main theme of the article, and measuring hypotheses developed from the literature in order to measure consumer perception a questionnaire survey was conducted and analyzed via SPSS 22.0 package program and the validity of hypotheses is tested. As a result, food products under GI protection makes many advantages by their own nature and encourages trade. Also they play an important role in city branding.